Meningkatkan Keterampilan Tata Kecantikan Merias Wajah Flawless Melalui Metode Explicit Instruction bagi Siswa Disabilitas Rungu (Classroom Action Research Kelas VIII di SLBN 2 Sawahlunto) - Puspa, Dara; Zulmiyetri, Zulmiyetri; Efrina, Elsa; Triswandari, Retno; Zulpiani, Mardhatillah (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the flawless makeup artistry skills of hearing-impaired students through the explicit instruction method. The study was conducted on two eighth-grade students at SLBN 2 Sawahlunto using a Classroom Action Research (CAR) approach in two cycles, each consisting of four meetings. Data collection techniques were carried out through observation, documentation, and performance assessment. The research results indicate a significant improvement in flawless makeup skills. The RRP skill score increased from 40.57% to 94.92% at the end of Cycle I, and reached 100% in Cycle II. VAP improved from 35.50% to 92.75% by the end of Cycle I, and reached 99.27% in Cycle II. Both students were able to complete all stages of makeup application independently with smooth, neat, and symmetrical final results. These findings indicate that the explicit instruction method is effective in enhancing beauty skills among hearing-impaired students.